THE ROLE OF TECHNOLOGY AND DIGITAL LITERACY IN IMPROVING STUDENT LEARNING MOTIVATION: A LITERATURE REVIEW 2021-2025 - Sulistiani; Bambang Subali; Ellianawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze trends, directions, and research findings highlighting the relationship between technology utilization, digital literacy, and learning motivation in the context of modern education. The method used was a systematic literature review, referring to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Of the 1,195 articles identified through various databases and research registers, 53 articles met the inclusion criteria and were analyzed in depth using a descriptive and thematic approach. The study results indicate that digital literacy plays a crucial mediating factor in optimizing the use of technology to enhance student learning motivation. The use of digital media, online learning platforms, and artificial intelligence (AI)-based technology has been shown to strengthen student engagement, increase curiosity, and foster learning independence. Furthermore, the application of technology also encourages the formation of a flexible and learner-centered learning ecosystem. This study recommends strengthening digital literacy, improving teachers' pedagogical and digital competencies, providing supporting infrastructure, and implementing differentiated learning strategies oriented toward motivation, creativity, and active student participation in the digital era.